Persepsi Kinestetik Terhadap Rangkaian Gerak Pada Alat Simpai Atlet Senam Rhytmik PERSANI Sulawesi Selatan - Ariana Asri; Haeril Haeril (Jendela Olahraga, 2022)
This study aims to determine the contribution of kinesthetic perception to the rhythmic gymnastic  movement structure of PERSANI's hoop in South Sulawesi. This research belongs to the type of descriptive research with quantitative methods. The population is PERSANI South Sulawesi rhythmic gymnast with a sample of 30 people. Data analysis techniques using descriptive analysis, normality test, linearity test, simple regression test using computer facilities through the SPSS program. Based on data analysis, the results obtained that there is a significant contribution of kinesthetic perception to the series of rhythmic gymnastics hoops with a coefficient of determination (R Square) of 0.630 (63%).